KONSEP DASAR KOMUNIKASI ORGANISASI PENDIDIKAN - Mahdayeni; Andika; Sarmiyati; Indini; Mahdayeni yeni (Jurnal Pelita Pendidikan, 2024)
AbstractThis article aims to determine the importance of communication of Islamic education organization using the literature and literary approach related to the theme of this research. The authors ' analysis results showed that organizational communication is indispensable in running an organization of Islamic educational institutions. The success of Islamic educational institutions is determined by the management and organanization factor and interpersonal communication skills owned by each stake holders in carrying out their duties. Effective communication can be seen from the best service and school management, the quality and excellence of graduates as the expectations of stakeholders, the communication skills for school personnel is indeed the task of managers and school leaders To always be enhanced to make it clearer the benefits or contributions of communication skills and effectiveness in realizing the achievement of educational objectives in Islamic educational institutions.Keywords: Communication, Organization, Education